Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/es0015444
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Aerosol Particles from Reactions of Secondary and Tertiary Alkylamines:  Characterization by Aerosol Time-of-Flight Mass Spectrometry

Abstract: In ambient field studies conducted with aerosol time-of-flight mass spectrometry (ATOFMS), individual particle mass spectra commonly contain ion peaks at mass/charge (m/z) 86, 101, 102, and 118. Particles with mass spectra containing these peaks show a strong correlation with high relative humidity and low temperatures. In an effort to identify these peaks, a series of smog chamber studies were conducted probing the chemistry of secondary and tertiary alkylamines. Specifically, in separate studies, trimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
251
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(270 citation statements)
references
References 28 publications
(32 reference statements)
17
251
1
1
Order By: Relevance
“…Mass-to-charge ratio þ59 is recognized as the dominant peak for TMA since it could not be produced from any other common amine species (Angelino et al, 2001;Rehbein et al, 2011). A total of 126,918 mass spectra for TMA-containing particles were obtained, which contributed approximately 18% on average to the total detected submicron particles by number.…”
Section: Detection Of Tma-containing Particles With Spamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass-to-charge ratio þ59 is recognized as the dominant peak for TMA since it could not be produced from any other common amine species (Angelino et al, 2001;Rehbein et al, 2011). A total of 126,918 mass spectra for TMA-containing particles were obtained, which contributed approximately 18% on average to the total detected submicron particles by number.…”
Section: Detection Of Tma-containing Particles With Spamsmentioning
confidence: 99%
“…Recent measurements by Silva et al (2008) showed that amines could account up to 20% of organic matter mass in fine aerosol during some wintertime periods in Utah, USA. Angelino et al (2001) reported that up to 80% of single particles contained amine signals during some episodes in Riverside, CA. To our best knowledge, amines in particulate phase were scarcely reported in China (Wang et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved to be a powerful tool for analyzing the mixing state and formation mechanisms of aerosols in single particle levels (Gaston et al, 2010;Angelino et al, 2001;Moffet et al, 2004;Freney et al, 2006;Denkenberger et al, 2007;Moffet and Prather, 2009;Wang et al, 2009a;Yang et al, 2009). These accomplishments are extremely helpful to understand the impact of aerosols on the global climate.…”
Section: Introductionmentioning
confidence: 99%
“…Time-of-flight mass spectrometry (TOFMS) is beginning to be applied in atmospheric chemistry to elucidate organic compounds including biomarkers, on single aerosol particles (Alvarez, Vezmar, & Whetten, 1998;Noble & Prather, 2000;Angelino, Suess, & Prather, 2001;Whiteaker & Prather, 2003). The organic matter of individual aerosol particles is vaporized by laser and ionized in the TOFMS.…”
Section: Time-of-flight Mass Spectrometrymentioning
confidence: 99%